A prospective clinical trial of the second‐look procedure for transoral surgery in patients with T1 and T2 laryngeal, oropharyngeal, and hypopharyngeal cancer. (8th October 2019) - Nishimura, Goshi; Sano, Daisuke; Arai, Yasuhiro; Hatano, Takashi; Takahashi, Hideaki; Tanabe, Teruhiko; Wada, Takashi; Morishita, Daiki; Oridate, Nobuhiko
Abstract: Background: Transoral surgery (TOS) has been widely applied for early T‐stage head and neck cancer (HNC). The resection is performed with a minimum safety margin for function preservation under a limited surgical field; therefore, it is difficult to have a strong conviction about the complete resection. This study aims to evaluate the completeness of the initial TOS procedure; possibility of primary control by TOS alone; and predictive factors in patients with early T‐stage laryngeal, oropharyngeal, and hypopharyngeal cancer. Methods: Patients were treated by TOS at the primary site with or without neck dissection. The patients were divided into two groups based on the pathological evaluation of their surgical specimens: the control (observation) group, in that the resection was considered complete and the intervention (second‐look procedure) group, in that incomplete tumor resection was suspected. The predictive factors for the possibility and/or limitations of complete resection by TOS were then analyzed. Results: The study enrolled 26 and 25 patients in the control and intervention group, respectively. The success rate for single resection was 66% and the predictive factor was tumor depth obtained by enhanced computed tomography (CT) examination (odds ratio, 7.870, P = .0243). The success rate for definitive therapy by TOS alone was 83% and the predictive factor was poor differentiation observed on pathological examination (odds ratio, 6.800, P = .0248). Conclusions: TOS has the potential for both definitive resection and function preservation with minimal invasiveness. Identification of the risk factors for TOS is advantageous for accurate treatment selection in patients with early T‐stage HNC. Abstract : Transoral surgery has the potential for both definitive resection and function preservation with minimal invasiveness. Identification of the risk factors for transoral surgery, such as tumor depth obtained by enhanced CT examination and poor differentiation observed on pathological examination, is advantageous for accurate treatment selection in patients with early T‐stage head and neck cancer.